Recent advances in the solar thermochemical splitting of carbon dioxide into synthetic fuels - Rony, Zahidul Islam; Mofijur, M.; Ahmed, Shams Forruque; Kabir, Zobaidul; Chowdhury, Ashfaque Ahmed; Almomani, Fares (Frontiers in Energy Research, 2022)
Recent years have seen a sharp rise in CO2 emissions into the atmosphere, which has contributed to the issue of global warming. In response to this several technologies have been developed to convert CO2 into fuel. It is discovered that the employment of a solar-driven thermochemical process (S-DTCP) that transforms CO2 into fuels can increase the efficiency of the production of sustainable fuels. The process involves the reduction of metal oxide (MO) and oxidizing it with CO2 in a two-step process using concentrated solar power (CSP) at higher and lower temperatures, respectively. This study summarizes current advancements in CO2 conversion methods based on MO thermochemical cycles (ThCy), including their operating parameters, types of cycles, and working principles. It was revealed that the efficiency of the solar conversion of CO2 to fuel is not only influenced by the composition of the MO, but also by its morphology as well as the available surface area for solid/gas reactions and the diffusion length. The conversion mechanism is governed by surface reaction, which is influenced by these two parameters (diffusion length and specific surface area). Solar energy contributes to the reduction and oxidation steps by promoting reaction kinetics and heat and mass transport in the material. The information on recent advances in metal oxide-based carbon dioxide conversion into fuels will be beneficial to both the industrial and academic sectors of the economy.